Difference of hemaglutinins between wild-type and vaccine measles virus in Indonesia - Made Setiawan; Agus Sjahrurachman; Fera Ibrahim; Agus Suwandono (Paediatrica Indonesiana, 2008)
Background Hemaglutinin (H) protein of measles virus is veryimportant in the process of host cell infection. H protein is alsoable to induce specific antibodies which can neutralize measlesvirus and block the cell infection.Objective This study aimed to explore the nucleotide and aminoacid sequence differences between wild-type measles virus (G2,G3 and D9) with CAM-70, Schwarz and Edmonston-wt vaccinevirus.Methods The exctration and amplification of the gene wereconducted in the laboratory using biomolecular technology. Thegene and protein analysis were conducted using the bioinformatictechnology.Results The results showed that the differences in nucleotidesequences were highest between wild-type virus and CAM-70vaccine virus (76-77 nucleotides), followed by Schwarz (61-64nucleotides) and Edmonston (60-63 nucleotides). The differencesin amino acid sequences were highest between wild-type virusand CAM-70 (24-29 residues), followed by Schwarz (13-20residues) and Edmonston (12-19 residues).Conclusion The Indonesian wild-type measles virus was geneticallycloser to Schwarz vaccine virus than CAM-70 vaccine virus,hence the neutralizing antibodies generated by Schwarz vaccinewere more specific against Indonesian wild-type virus comparedto CAM-70 vaccine.